Terrain : the houseplant book : an insider's guide to cultivating and collecting the most sought-after specimens - Lowrie, Melissa; Lees, Caroline (Copywriter) (Artisan, 2022)
"A book of tips and tricks from seasoned professionals for making plants happy in their homes and styling advice from the designers who created that signature Terrain look"--